The Perspective of Consumers and Retailers in the Emerging Mall Culture - Bawa, Ramandeep; Sinha, Anil Kishore; Kant, Rita (Current Progress in Arts and Social Studies Research Vol. 4, 2024)
Malls are attracting young shoppers and mall culture is new to the society. Mall retailers are making efforts to satisfy young consumers. However, the younger segment is growing in terms of population and wealth. It has become increasingly important and necessary to understand and meet their demands. The study employed 160 in-depth interviews to understand the young consumers’ mall experiences. The researchers also interviewed 191 retailers to analyse the problems faced with regard to the facilities, services and rules implemented by the authorities. Overall, the researcher found eight elements that are important for young consumers to form an impression of the shopping malls: convenience, choice, awareness, crowded/congested, ambience, parking, hedonic shopping and mall culture. Respondents also highlighted various attributes such as sitting arrangement, water dispensers, E-mapping, plain ramps, and book browsing section and further expressed their concern regarding parking, security and customer service. The perspective of retailers was studied. Few malls didn’t flourish as brand stores have a policy of not opening retail outlets within a radius of 3 km. Research should be undertaken before a Mall is being built so that all these issues can be rectified below and will save malls from becoming vacant. The results can help mall retailers capitalise on the consumers by meeting their needs.